Manajemen Pengembangan Bakat Tunarungu Di SMA LB Negeri Tamanwinangun Kebumen - Khasanah, Siti Nur; Chamidi, Agus Salim (IAINU Kebumen, 2024)
The background of this research is that LB Negeri Tamanwinangun High School is the only special public school in Kebumen district which has seven skills areas to cover the talent development of students with special needs. The purpose of this study was to determine the management of talent development starting from the planning process, the organizing process, the implementation process, and the evaluation process in developing the talents of deaf students at SMA LB Tamanwinangun Kebumen. This research is a qualitative research using a case study approach. The subjects of this study were school principals, vocational advisors, and deaf students at SMA LB Negeri Tamanwinangun Kebumen. Data collection techniques used by researchers are observation, interviews, and documentation. The data analysis technique used is the theory of Miles and Huberman, namely data reduction, data presentation and verification or drawing conclusions. Based on the results of the study, it can be concluded that the management of deaf talent development at Tamanwinangun Kebumen State LB High School, namely: 1) The planning process is carried out at the annual meeting which discusses planning for the distribution of skill supervisors, planning for the preparation of work programs by each skill supervisor teacher, planning funds for facilities and infrastructure, and planning evaluation activities. 2) The organizing process is carried out directly by the school principal regarding the division of supervisors in skills areas by taking into account the interests and talents of each supervising teacher. After that, training was conducted for each supervising teacher in that skill field. 3) The process of developing the talents of deaf students begins with identifying the talents of students by distributing questionnaires and considering the abilities of students, after which each student is grouped according to the skill area that has been selected. This process is carried out every Tuesday and Wednesday from 07.30 to 14.00 WIB and carried out in the respective skill areas. The method used in talent development uses a personal approach method with simple sign language. 4) The evaluation process carried out by the school uses two methods, namely the observation method and the measurement method. The observation method is carried out by the supervising teacher during the activity and the measurement method is carried out when there is a practical exam. And reported at the annual meeting held